A Comparative Analysis of Genetic and Epigenetic Factors in METH Addiction: A Focus on SLC (SLC6A4) and COMT Genes - Haider K. Hussain; Yolanda Loarce Tejada; Anna Barbaro (Frontiers in Bioscience-Landmark)
Background: Methamphetamine (METH) addiction is a global concern due to its severe impact on public health, including heightened aggression and neurotoxic effects. Genetic and epigenetic factors, particularly involving the SLC6A4 and COMT genes, are implicated in individual vulnerability to METH addiction. Thus, understanding the molecular mechanisms involved is crucial for developing targeted prevention and treatment strategies. Methods: A systematic literature review was conducted following the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines. Six major databases (MEDLINE/PubMed, Scopus, ScienceDirect, ResearchGate, Web of Science, Google Scholar) and Spanish-language platforms (Dialnet, Redalyc, CSIC, RECyT) were searched for studies published in English, Spanish, and Portuguese over the last 40 years. The inclusion criteria encompassed original research focusing on genetic and/or epigenetic determinants of METH addiction, with particular emphasis on the SLC6A4 and COMT genes. Studies focusing on substances other than METH, non-human subjects, or those that did not meet the language or temporal restrictions were excluded. Data on genetic variants, epigenetic alterations (e.g., DNA methylation, histone modifications), and relevant behavioral outcomes were extracted. Results: From an initial 600 articles, 25 studies met the inclusion criteria and were included in the qualitative synthesis. Polymorphisms in SLC6A4 (e.g., 5-HTTLPR) were associated with an increased risk of METH addiction (odds ratio (OR) = 2.31, 95% confidence interval (CI): 1.45–3.68; p = 0.001); meanwhile, variations in COMT (Val158Met) were linked to both susceptibility and executive function deficits. Epigenetic modifications—most notably DNA methylation in SLC6A4 and COMT—also emerged as important contributors to addiction pathways, potentially influencing dopamine and serotonin regulation. Gene-environment interactions, including factors such as childhood trauma and socioeconomic status, were found to modulate genetic predispositions, suggesting a multifaceted etiology for METH dependence. Conclusions: Both genetic polymorphisms and epigenetic alterations play a critical role in METH addiction vulnerability. The reviewed evidence highlights the need for more comprehensive, regionally diverse studies and integrative approaches that combine genetics, neurobiology, and psychosocial factors. Such strategies could inform personalized prevention and treatment interventions, improving patient outcomes and mitigating the global burden of METH addiction.